Review on green and chemical fabrications of zinc oxide nanoparticles: synthesis and its biological activity - Ribut, Siti Huzaimah; Che Abdullah, Che Azurahanim; Mohd Yusoff, Mohd Zaki (2018)
The physicochemical techniques of the synthesis of zinc oxide nanoparticles (ZnONPs) have been reviewed. Through this review, we able to distinguish the properties of ZnONPs obtained when synthesis using chemical and green synthesis method. Currently, the green synthesis method is preferable by researcher owing to the environmentally friendly and can reduce the non-toxic substances usage. The green synthesis method used several natural sources and involved in various biological and physical activity like photocatalytic, antibacterial, antifungal, antioxidant, and cytotoxicity test to show the role of ZnONPs in various aspects.